Impact of school adjustment and study habits on English language achievement among senior secondary students - SOHAN SINGH; SINGH, DILIP KUMAR (Journal of Interdisciplinary Studies in Education, 2024)
In the present study, we aim to investigate the impact of school adjustment and study habits on English language achievement among senior secondary students. This study is contrary to expectations; neither school adjustment nor study habits individually demonstrated a significant correlation with English language achievement. However, the combined effect of both factors revealed by regression analysis was significant at the 0.05 level, suggesting that they collectively contribute to predicting English language proficiency. These findings highlight the complex interplay of factors that influence language learning and the importance of considering multiple influences beyond individual variables.